Effect of seed mass and storage period on germination and seedling growth of the mango ’Espada’ - Borges, Carlos Alexshander Macêdo; Siqueira, Dalmo Lopes de; Dias, Denise Cunha Fernandes dos Santos; Cardoso, Antônio Américo (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to evaluate the effect of seed mass and storage period on seed germination and seedling growth of the mango ’Espada’. Seeds were classified in three classes: I (up to 15.5 g), II (15.6 to 19.0 g) and III (over 19.0 g) and stored for 0, 7, 14, 21 and 28 days. The experiment was arranged in a completely randomized design, and the treatments consisted of the mass classes. Germination percentage, germination velocity index, stem height and diameter, number of leaves and dry matter mass of the aerial parts of seedlings were evaluated. Seed mass did not affect germination. ’Espada’ mango seeds must not be stored.